Interstitial Lung Disease Induced by Crizotinib in Non-Small-Cell Lung Cancer - Tereso, Andreia (2019)
The treatment of advanced non-small-cell lung cancer shifted with the development of molecular-targeted therapies, like the tyrosine kinase inhibitors. One example of tyrosine kinase inhibitors is crizotinib, an anaplastic lymphoma tyrosine kinase inhibitor, which targets an echinoderm microtubule-associated protein-like-4-anaplastic lymphoma kinase gene fusion. This mutation is found in only 2% to 7% of non-small-cell lung cancer cases. Although these new therapies have shown promising results, the occurrence of interstitial lung disease as a side effect could be problematic. As the diagnosis of drug-related-interstitial lung disease is difficult to make, computed tomography is an important diagnostic tool. The recognition of computed tomography manifestations of tyrosine kinase inhibitors -induced interstitial lung disease is the key for an early recognition and management of this pulmonary toxicity. We aim to raise awareness of tyrosine kinase inhibitors-induced interstitial lung disease, by reporting the first case of a Portuguese patient treated with crizotinib for non-small-cell lung cancer who developed drug-induced interstitial lung disease.